PERSISTENT INFECTIONS IN PEDIATRICS (World Bulletin of Public Health, 2024)
The clinical and social significance of persistent infections remains relevant. The main aspects of this pediatric problem are: epidemiology and pathogenesis of persistent infections, clinical manifestations, possibilities of treatment and prevention, predictions of active reproduction of infectious agents
Keywords: children; herpes simplex virus; human immunodeficiency virus; cytomegalovirus